Effects of Exosomes on Neurological Function Recovery for Ischemic Stroke in Pre-clinical Studies: A Meta-analysis - Huang, Mudan; Hong, Zhongqiu; Xiao, Chongjun; Li, Lili; Chen, Lilin; Cheng, Shimei; Lei, Tingting; Zheng, Haiqing (Frontiers in Cellular Neuroscience, 2020)
Background: Exosomes, especially stem cell-derived exosomes, have been widely studied in pre-clinical research of ischemic stroke. However, their pooled effects remain inconclusive. Methods: Relevant literature concerning the effects of exosomes on neurological performance in a rodent model of ischemic stroke was identified via searching electronic databases, including PubMed, Embase, and Web of Science. The primary outcomes included neurological function scores (NFS) and infarct volume (IV), and the secondary outcomes were several pro-inflammatory factors and terminal deoxynucleotidyl transferase deoxyuridine triphosphate nick end labeling-positive cells. Subgroup analyses regarding several factors potentially influencing the effects of exosomes on NFS and IV were also conducted. Results: We identified 21 experiments from 18 studies in the meta-analysis. Pooled analyses showed the positive and significant effects of exosomes on NFS (standardized mean difference −2.79; 95% confidence interval −3.81 to −1.76) and IV (standardized mean difference −3.16; 95% confidence interval −4.18 to −2.15). Our data revealed that the effects of exosomes on neurological outcomes in rodent stroke models might be related to routes of administration and exosomes sources. In addition, there was significant attenuation in pro-inflammatory factors, including interleukin-6, tumor necrosis factor-α and interleukin-1β, and terminal deoxynucleotidyl transferase deoxyuridine triphosphate nick end labeling-positive cells when undergoing exosomes treatment. Conclusion: Cell-derived exosomes treatment demonstrated statistically significant improvements in structural and neurological function recovery in animal models of ischemic stroke. Our results also provide relatively robust evidence supporting cell-derived exosomes as a promising therapy to promote neurological recovery in stroke individuals.